(untitled) (Research, Society and Development, 2021)
Platelet-rich fibrin (PRF) is a blood concentrate produced in a totally natural way, without the use of anticoagulants. This concentrate is applied with the objective of promoting acceleration in the healing of soft and hard tissues. In dentistry, this biomaterial has been used in several procedures. The present work was developed with the objective of describing a clinical case in which PRF and liquid PRF membranes associated with lyophilized bovine bone were used in the treatment of a patient with atrophic maxilla to enable implant installation and prosthetic rehabilitation. Given the results of the clinical case presented, it can be concluded that the use of PRF has a favorable result in the regeneration of bone and gingival tissues. When associated with graft material, it accelerates the healing process, in addition to assisting in the maturation of the graft, promoting an increase in bone volume, favoring the installation of implants and prosthetic rehabilitation.